Peranan Lembaga Bantuan Hukum Dalam Penanganan Anak Yang Berhadapan Dengan Hukum di LBH Apik Bali - Ni Putu Ayu Prasetya Paramita; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2021)
Law violations continue to increase every year, even children become lawbreakers. Children as the next generation must be protected. Because Indonesia is a State of Law. Then the Law on Legal Aid provides legal protection for the poor. The problems of this study are 1) what is the role of LBH APIK BALI in dealing with ABH? 2) What is the effectiveness of the APIK BALI LBH in handling ABH? The research method used in this paper is empirical, namely primary data sourced from research in the field and secondary data sourced from library research in the form of legal materials. The results of the study can be concluded that: 1) LBH APIK BALI in dealing with ABH by providing assistance to children in the Litigation and Non Litigation circles. 2) LBH APIK BALI in handling ABH has not been effective, but it is in accordance with the SPPA Law. The importance of cooperation, lobbying with the government to protect ABH so that the rights of the ABH regarding the provision of legal assistance in the LBH APIK BALI are fulfilled.Keywords: Role, Legal Aid Institution, Child Criminal Justice System